Do computers enable mathematical problem solving or just make it “EASY”? - Abramovic, Sergei (Computer Tools in Education, 2017)
This article suggests that recent advances in the development of computer programs capable of intricate symbolic computations might afford some negative outcomes by unintentionally shielding the learners of mathematics from all the challenges that are at the cornerstone of the subject matter. To address this concern, the paper describes how traditional curriculum can be modified in order to turn computer tools into enablers of problem solving. As an example of a new type of problem, the paper shows how the appropriate use of technology allows for some uncommon inquiries in the classic context of Fibonacci numbers. The article is written against the backdrop of mathematics teacher education.